Installation Of A State-Of-The-Art Ventilation Shaft At A New Mexico Coal Mine - S. L. Bessinger; T. A. Palm; A. Zeni (Society for Mining, Metallurgy & Exploration, 2006)
San Juan Coal Company (SJCC) operates an underground coal mine near Farmington, New Mexico. Continuous miners and a longwall produce 7-8 million tons per year. The coal seam at SJCC has tested to have a propensity for spontaneous combustion. As such, during feasibility for this project, it was elected to utilize a bleederless ventilation system on the longwall. Three-entry gateroads are developed, and the longwall gob is sealed as mining progresses. SJCC utilizes a nitrogen injection system to continuously inertize the gob. In 2004, the mine was nearing completion of its first longwall district. The next district would contain longer panels (up to 12,500 feet). Due to the liberation of methane, and to a lesser extent hydrogen sulfide, a typical wrap-around ventilation system would not be appropriate. Not only would gas concentrations likely be challenging, but the overall ventilating pressure in the mine would have to be increased beyond limits established to mitigate the potential for spontaneous combustion. Given the above-described operating constraints, SJCC determined a need for a small ventilation shaft in the back (longwall setup area) of the next district that would draw adequate air past the longwall seals to maintain low gas levels and permit the required regulatory inspections to occur. Extensive ventilation modeling and gas desorption testing indicated that the shaft would be required to handle a volume of air ranging from 40,000 cfm to as high as 185,000 cfm. This large range is driven by the position of the longwall face with respect to the shaft and the effectiveness of the SJCC degasification program (SJCC uses vertical gob vent boreholes and horizontal in-seam methods). Ventilation simulations determined an appropriate diameter for the 350-ft-deep shaft to be 5 feet. Having determined shaft size, the next decision related to the method of shaft construction. Conventional shaft sinking was ruled out, due to the small diameter. Raise boring was an attractive option but had two drawbacks: (1) development crews would reach the bottom of the shaft just a few weeks before longwall startup, leaving a compressed timeframe to install the shaft, and (2) raiseboring requires additional underground entries to be developed to stow the project’s cuttings. While raiseboring remained a viable option, the problems associated with it led SJCC to also investigate blind drilling.